Tinjauan Teologi Kontekstual terhadap Budaya SIJAGARON (Simbol dalam Upacara Kematian Adat Batak Toba) (Jurnal Pendidikan Agama dan Teologi, 2025)
The Toba Batak culture has a strong symbolic richness, especially in the traditional rituals of death which are full of theological and social meanings. One of the important symbols in the ceremony is Sijagaron, which literally means "guard" or "escort", and is used as a symbol of final respect to the deceased. This research aims to examine the meaning of Sijagaron through a contextual theological approach, by looking at how this symbol can be understood in the light of the Christian faith and its relevance in the lives of Toba Batak believers today. The method used is a descriptive qualitative study with a theological and anthropological approach. The results of the study show that Sijagaron contains Christian values such as love, fellowship, and respect for God's creation. From a contextual theological perspective, Sijagaron can be interpreted as a bridge between faith and culture, which shows that local cultural symbols can be a means of contextual evangelism. Thus, the culture of Sijagaron does not contradict the Christian faith, but rather enriches the people's understanding of the mystery of death and eternal life.